Nivel de conocimiento estudiantil y actitud familiar frente al embarazo precoz en alumnas del colegio Camilo Gallegos Domínguez año 2015 - Álvarez Sisalima, Nelson Fabián (2015)
According concept of World Health Organization (WHO) defines adolescence as the period of life in which the individual acquires the reproductive capacity, passes the psychological patterns from childhood to adulthood and independences trengthens the socio - economic and fixed limits between 10 and 19 years.